Pengaruh Literasi Keuangan Syariah Terhadap Keputusan Pemilihan Produk Simpanan BMT Rukun Abadi (Studi Kasus Anggota Koperasi BMT Rukun Abadi) - Robet Andika Saputra; Hendra Maulana; Diana Farid; Lina Marlina Susana; Heni Mulyasari; Muhammad Husni Abdulah Pakarti; Hendriana Hendriana (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to investigate the Effect of Sharia Financial Literacy on the Decision to Choose BMT Rukun Abadi Saving Products. This case study focuses on members of BMT Rukun Abadi Cooperative, which is a sharia-based financial institution in Indonesia. Islamic financial literacy is an important factor in encouraging the growth and development of the Islamic financial system. The research method used is a quantitative approach by distributing questionnaires to members of the BMT Rukun Abadi Cooperative. This questionnaire was designed to measure the level of Islamic financial literacy of the members as well as evaluate the decision patterns for choosing deposit products at BMT Rukun Abadi. The results showed that Islamic financial literacy has a significant influence on the decision to choose deposit products at BMT Rukun Abadi. Members of BMT Rukun Abadi Cooperative who have a higher level of Islamic financial literacy tend to be better able to understand the characteristics and benefits of Islamic savings products, so they can make more informed and effective decisions. These findings provide important implications for BMT Rukun Abadi in improving Islamic financial literacy services and education to its members. By improving Islamic financial literacy, members will be more engaged and involved in utilizing the Islamic savings products offered by this financial institution, thus supporting the growth and sustainability of the Islamic financial system in Indonesia.